Optimalisation Strategy For Light Intensity In Solar Cells To Improve Energy Efficiency - Siagian, Parlin; Alam, Hermansyah; Fahreza, Muhammad; Frasasti, Ridho Anggu (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study explores the optimisation of light intensity on solar cells to improve their energy efficiency. With the increasing global demand for energy and environmental issues due to dependence on fossil fuels, renewable energy sources, particularly solar energy, have become important. However, the efficiency of solar cells remains a challenge, with typical commercial efficiency ranging from 15% to 22%. This research investigates the impact of light intensity on solar cell performance and identifies strategies to optimise it. Factors such as semiconductor material quality, panel angle and orientation, and external conditions like weather and pollution are considered. The study shows that optimising light intensity can significantly enhance the energy conversion efficiency of solar cells. Methods such as using mirrors to concentrate sunlight and adjusting panel positions are explored to maximise light intensity. These findings contribute to the development of more efficient solar cell technology, aiding the broader adoption of clean energy solutions.